Score A Today / Thiru Selvan Devindran, Angela Tan Zhi Shinq and Lee Jin Cheng - Devindran, Thiru Selvan; Tan, Angela Zhi Shinq; Lee, Jin Cheng (Faculty of Computer and Mathematical Sciences, 2021)
Beginning from 21st century, education is much importance in our life. The development of science and technology has been widely used in different fields. Flexible use of technology can bring a lot of convenience to our lives. So, why not we bring in technology to education with some interesting colours and creative elements. Our system has many learning materials can be found according to personal needs. In addition, the website also provides other students to contribute their own notes and exercises. All the information will be reviewed by the administrator and then released. Therefore, this learning system is very comprehensive and positive. After applying our system: - More students are willing to learn. - Students can learn all the time. - If you encounter problems in schoolwork, you can discuss with everyone. - Students and parents can more easily know the progress and understanding of students in classes. - Save time because our system is simple to use and complete. Our system will achieve this by: - Administrator prepared notes, quiz and studies videos for the beginning of our system. - Personal account with personal information. - Complete social/chat system, like attendance and progress learning form. - Submission system. - AI system to check and mark students work. If the system can be successfully developed, this system can benefit all students, teachers and even parents. The system will be improved and strengthened at the future.